2004
DOI: 10.1002/cncr.20327
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of CARM1, a transcriptional coactivator of androgen receptor, in the development of prostate carcinoma and androgen‐independent status

Abstract: BACKGROUND Coactivator‐associated arginine methyltransferase 1 (CARM1) is a transcriptional coactivator of the androgen receptor (AR). It is involved in the regulation of the biologic functions of the AR. It remains to be determined whether CARM1 is involved in prostatic carcinogenesis. METHODS The expression of CARM1 in normal prostate epithelium, high‐grade prostatic intraepithelial neoplasia (PIN), and prostate carcinoma tissue was examined in 66 previously untreated patients with prostate carcinomas, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 28 publications
5
109
2
3
Order By: Relevance
“…Thus, ACTR͞AIB1 is amplified and͞or overexpressed in various carcinomas, including 30% of breast tumors of various grades, where it affects both estrogen-receptorand E2F-dependent transcriptions (18,40,41). Similarly, CARM1 was recently found to be overexpressed in androgen-independent prostate carcinomas (48). Here, we conducted a pilot experiment on breast tumor specimens of various grades and found cooverexpression of CCNE1, ACTR, and CARM1 genes in grade-3 tumors.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, ACTR͞AIB1 is amplified and͞or overexpressed in various carcinomas, including 30% of breast tumors of various grades, where it affects both estrogen-receptorand E2F-dependent transcriptions (18,40,41). Similarly, CARM1 was recently found to be overexpressed in androgen-independent prostate carcinomas (48). Here, we conducted a pilot experiment on breast tumor specimens of various grades and found cooverexpression of CCNE1, ACTR, and CARM1 genes in grade-3 tumors.…”
Section: Discussionmentioning
confidence: 67%
“…The arginine methyltransferase, CARM1/PRMT4, has been shown to regulate important cellular processes such as pluripotency maintenance (16,32), differentiation (6,15,17), splicing (18), and transcriptional activation (10 -14), as well as tumor manifestation and progression (33,34). However, the methyltransferase activity of this coactivator has been linked with only a few cases of transcriptional activation, muscle and thymocyte differentiation, and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the fact that PRMT1 and CARM1 can act as coactivators of nuclear receptors makes them likely candidates to be overexpressed in hormone-dependent cancers, including breast cancer (2). Indeed, it has been found that CARM1 overexpression correlates with androgen independence in human prostate carcinomas (73,74). It has also been observed that increased methylation of a PRMT6 substrate correlated with breast tumors of higher metastatic potential (75,76).…”
Section: Complex Genomic Structure At the 5ј-end Of The Prmt1 Gene Lementioning
confidence: 99%